2008
DOI: 10.1002/ejsp.552
|View full text |Cite
|
Sign up to set email alerts
|

Fitting in with the flock: Social attractiveness as a mechanism for well‐being in religious groups

Abstract: For most people, religion is practiced and experienced within a social group of believers who interact regularly. Yet the role of social psychological intergroup processes has largely been ignored with respect to religious phenomena. The present study explores social attraction as a mechanism by which religious groups affect the psychological well-being of their members. Data were taken from a large survey of the members of 411 religious congregations in the United States. Linear mixed modeling analyses were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 45 publications
4
25
0
Order By: Relevance
“…Some have attempted to integrate the incongruent findings, suggesting that sharing mystical beliefs might be a social investment that engenders trust and support and signals group membership (Hayward & Elliott, 2009;Sosis, 2004). Thus, spirituality may simultaneously be costly and beneficial (akin to insurance policies that require outlays for premiums while simultaneously offering reassurance).…”
Section: Spirituality and Psychological Well-beingmentioning
confidence: 96%
See 1 more Smart Citation
“…Some have attempted to integrate the incongruent findings, suggesting that sharing mystical beliefs might be a social investment that engenders trust and support and signals group membership (Hayward & Elliott, 2009;Sosis, 2004). Thus, spirituality may simultaneously be costly and beneficial (akin to insurance policies that require outlays for premiums while simultaneously offering reassurance).…”
Section: Spirituality and Psychological Well-beingmentioning
confidence: 96%
“…For example, implicit priming experiments find religious salience reduces cheating (Randolph-Seng & Nielsen, 2007): supporting the idea that mystic belief may be a culturally specific cue for initiating prosocial behavior. Still others have described religious practice as a means of displaying social fit (Hayward & Elliott, 2009). In a larger meta-analysis, Smith et al (2003) found religiosity negatively predicts depression (r 5 À.10) and acts as a buffer against stress.…”
Section: Spirituality and Psychological Well-beingmentioning
confidence: 97%
“…If the dissonance cannot be resolved (e.g., by concluding that the universe is not justly governed or that the observed suffering is justified) then one's well-being is likely to be negatively affected. These effects may be exacerbated for members of religious groups that make unwavering belief an important element of the group identity-if prototypically ''good'' group members should always be certain of their beliefs, then doubt may be harmful because it alienates one from the group and its positive aspects (Hayward & Elliott, 2009). Consistent with the perspective that religious doubt may be harmful, several studies directly assessing well-being outcomes have found that religious doubt is related to worse self-reported physical health (Krause & Wulff, 2004) and more risk of a variety of mental health problems (Galek, Krause, Ellison, Kudler, & Flannelly, 2007).…”
mentioning
confidence: 95%
“…For example, there is greater concern in the Jewish tradition for adhering to the correct religious practices than in holding the right beliefs (Cohen, 2002), and questioning of orthodoxy is encouraged in the Unitarian-Universalist tradition (Elliott & Hayward, 2007). To the extent that the negative effects of doubt are predicated on group identity processes, such as a feeling of reduced fit with group norms that leads to anticipating conflict or lack of support from other members (Hayward & Elliott, 2009), they may be less severe in contexts where orthodoxy is less central. In those cases, other factors that undermine the worldview might play a bigger role in coping with bereavement, such as perceptions of not having fulfilled one's ritual or moral obligations.…”
mentioning
confidence: 98%
“…However, the characteristics of and relationships among those constituting a religious community may vary dramatically. Acknowledging this fact, several researchers have recently called for more investigation into how these different interpersonal dynamics may influence individual congregants (Graham & Haidt, 2010;Hayward & Elliott, 2009;Meagher & Kenny, 2013).…”
mentioning
confidence: 98%